Feasibility study of bongo village, gorontalo district as a religious tourism destination - Yumanraya Noho; Lisna Bantulu (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
This study aims to assess the feasibility of Bongo Village in the Gorontalo Regency as a religious tourism destination. The method used uses a qualitative descriptive approach by using Islamic religious tourism indicators, including tourists' motivation to visit Bongo Village, the behaviour of tourists while in tourist objects, the availability of halal food and drinks, and the availability of halal accommodation. The study results found that the application of religious tourism indicators in Bongo Village still experienced several obstacles, including the behaviour and ways of dressing some tourists and local people who were not following Islamic law. No accommodation was following the standard of halal accommodation according to international rules. However, in terms of tourism activities, several activities represent religious tourism activities where some tourists visiting Bongo Village are to study religious histories such as studying the Walima tradition as the Prophet's Birthday Commemoration and the activities of Pesantren Alam. In terms of food provision, several food stalls in Bongo Village have provided halal food. However, a halal certification from the MUI still has to be supported to ensure the trust of Muslim tourists when visiting Bongo Village.